Comparison of factors associated with disordered eating between male and female Malaysian university students - Chin, Yit Siew; Appukutty, Mahenderan; Kagawa, Masaharu; Gan, Wan Ying; Wong, Jyh Eiin; Poh, Bee Koon; Mohd Shariff, Zalilah; Mohd Taib, Mohd Nasir (MDPI, 2020)
Disordered eating is prevalent among university students, especially females. Whilst literature suggests that factors associated with disordered eating may differ according to gender, such an association has not been studied in Malaysia. This cross-sectional study aims to compare factors associated with disordered eating between male and female university students. A total of 716 university students (male: 27.4%; female: 72.6%) were recruited in Kuala Lumpur and Selangor, Malaysia. All participants completed a set of self-administered questionnaires and their body weight and height were recorded. About one in five of the university students (20.3%) were found to have disordered eating. There were more female students (22.9%) disordered eating compared to males (13.3%, χ2 = 8.16, p < 0.05). In male students (β = 0.228, p < 0.01), depressive symptoms were the only significant predictor for disordered eating. In females, the strongest predictor was depressive symptoms (β = 0.214, p < 0.001), followed by body size satisfaction (β = −0.145, p < 0.01) and body appreciation (β = −0.101, p < 0.05). These findings suggest that there are gender differences in the factors associated with disordered eating among Malaysian university students. Intervention programmes that address disordered eating should take into account these sex differences and its contributing factors.